Lift and drag improvements of airfoil through utilization of rough surface at trailing edge - Mahmud, Abdullah Saad (2014)
It is well known that roughness effect is detrimental for the aerodynamics performance of a surface or airfoil in the sense that it produces higher drag and lower lift. However, literature study lead to the understanding (fact) that in low subsonic regime for free stream velocity Reynolds number between 104 to 106, the lift to drag ratio of smooth and rough airfoil exhibit striking difference; L/D of smooth airfoil increases non-linearly with Reynolds number while for rough airfoil it increases only linearly. In addition between Reynolds number 104 to 105, the rough airfoil has better L/D values. Some other researchers have also confirmed such behaviour, however, the details of the roughness characteristic is not well defined. It will be of interest how the distribution of surface roughness along the airfoil will influence such aerodynamics performance gain. It is with such motivation that in this research, a set of experiments are used to determine the effects of surface roughness at the trailing edge of an airfoil with low subsonic free stream velocity (Reynolds number, Re, less than 106) conditions. Some additional information may be useful in the present study; a numerical study is available in literature, which could be used for validation and comparison. The problem statement above is further limited to laminar flow which is considered to prevail in flight vehicles flying in this Reynolds number range, particularly UAV, and for Wind-Turbine blades. Experimental work is carried out for this purpose using an airfoil which is specifically designed and built and using a wind tunnel with 1 by 1m cross-section and Reynolds number 4.29×105 and 5.65×105, which is considered to be typical and appropriate for the study. In addition, measurements are carried out using PIV technique and flow visualisation. Results obtained confirms the behaviour identified here. In addition, several other interesting and beneficial aerodynamic characteristic are revealed and elaborated. Overall the result obtained is considered to meet the objectives of the research as well as novelty, such as through improved design configurations of the trailing edge roughened surface.